Histological Changes of the Mucosal Epithelium in the Chicken Intestine during Pre- and Post-Hatching Stages - Md. Al amin; Md Badiul Alam; Kohzy Hiramatsu (The Journal of Poultry Science)
This study clarified the histological changes in the mucosal epithelium of the chicken intestine during the pre- and post-hatching stages. The duodenum, jejunum, ileum, and colorectum were collected from embryos at 15, 17, 18, 19, and 21 days of incubation and from chicks at 1 and 3 days after hatching. Paraffin sections prepared from tissue samples were stained with periodic acid-Schiff followed by alcian blue for histological analysis and to detect goblet cells. Villin and β-actin were detected using double immunofluorescence. Villi with finger-like shape were already observed in embryos after 15 days of incubation, and no obvious change in shape was observed even after hatching. Villous height increased in all intestinal regions as the developmental stage progressed, particularly a few days before and after hatching. Goblet cells first appeared in the epithelium of all intestinal regions after 18 days of incubation. The density of goblet cells rapidly increased from 18 to 21 days of incubation. Both villin and β-actin immunoreactivities were detected at the apical surface of the villous epithelium in all intestinal regions, and villin immunopositivity was stronger in the jejunum and ileum after hatching. These findings indicate that the villi and microvilli of the intestine of broiler chickens show histological changes during few days just before and after hatching. Additionally, the density of goblet cells rapidly increased for a few days before hatching.